RELATIONSHIP BETWEEN DIURETIC RELATED HYPERURICEMIA AND CARDIOVASCULAR EVENTS: DATA FROM THE URRAH (URIC ACID RIGHT FOR HEART HEALTH) STUDY. (April 2021) - Maloberti, Alessandro; Bombelli, M.; Facchetti, R.; Virdis, A.; Casiglia, E.; Tikhonoff, V.; Barbagallo, C.m.; Cirillo, M.; Desideri, G.; Ferri, C.; Galletti, F.; Iaccarino, G.; et al.
Abstract : Objective: Hyperuricemia can be both determined by overproduction (due to xanthine oxidase hyperactivity) or renal hypoexcretion. In this latter case, also diuretic use (particularly hydrochlorotiazhide) can be involved. While the relationship between hyperuricemia and CardioVascular (CV) events has been definitively linked in many studies, data on diuretic related hyperuricemia are still lacking. The objective of this analysis is to assess the relationship between diuretic induced hyperuricemia and CV events. Figure. No caption available. Design and method: The URic acid Right for heArt Health study is a nationwide, multicentre, observational cohort study involving data on individuals aged 18–95 years recruited on a regional community basis from all the territory of Italy under the patronage of the Italian Society of Hypertension with a mean follow-up period of 122 ± 66.9 months. Patients were classified into four groups accordingly to the diuretic use (yes vs no) and Uric Acid (UA) levels (higher or lower than the median value of 4.9 mg/dL). All cause death, CV deaths and CV events were consiedered as outcomes. Results: A total of 17747 individuals were included in the analysis. Mean age was 57.1 ± 15.2 years, males were 45.3%, SBP/DBP were 144.1/85.2 ± 24.6/13.2. 17.2% of the subjects use diuretic of whom 58% presents UA higher than median values. As showed in figure 1, patients with Hpeuricemia without diuretic use served as reference group. In multivariate adjusted analysis (for sex, age, SBP, BMI, glycemia, total cholesterol and creatinine) subjects without hyperuricemia and without diuretic show a significant lower risk for the three outcomes. Subjects without hyperuricemia with diuretic use have lower risk of all cause death but similar risk of CV death and events. Finally subjects with hyperuricemia and diuretic use exhibit a similar risk for the three outcomes as compared with the reference group. Conclusions: Our study showed that diuretic related hyperuricemia is related to CV events similarly to the subjects that present hyperuricemia without diuretics.